Echocardiographic Assessment of Cardiac Function in Pediatric Survivors of Anthracycline-Treated Childhood Cancer. (December 2019) - Slieker, Martijn G.; Fackoury, Cheryl; Slorach, Cameron; Hui, Wei; Friedberg, Mark K.; Fan, Chun-Po Steve; Manlhiot, Cedric; Dillenburg, Rejane; Kantor, Paul; Mital, Seema; Liu, Peter; Nathan, Paul C.; et al.
Abstract : Background: Anthracycline-induced cardiotoxicity is a major cause of morbidity and mortality in childhood cancer survivors (CCSs). Echocardiographic myocardial strain imaging is recommended in adult patients with cancer, but its role in pediatric CCSs has not been well established. Aims of this study were to determine the prevalence of abnormalities in left ventricular strain in pediatric CCSs, to compare strain with other echocardiographic measurements and blood biomarkers, and to explore risk factors for reduced strain. Methods: CCSs ≥3 years from their last anthracycline treatment were enrolled in this multicenter study and underwent a standardized functional echocardiogram and biomarker collection. Regression analysis was used to identify factors associated with longitudinal strain (LS). Results: Five hundred forty-six pediatric CCSs were compared with 134 healthy controls. Abnormal left ventricular ejection fraction (<50%) and mean LS ( Z score, <−2) was found in 0.8% and 7.7% of the CCSs, respectively. LS was significantly lower in CCSs than in controls, but the absolute difference was small (0.7%). Lower LS in CCSs was associated with older current age and higher body surface area. Sex, cumulative anthracycline dose, radiotherapy, and biomarkers were not independently associated with LS. Circumferential strain, diastolic parameters, and biomarkers were not significantly different in pediatric CCSs. Conclusions: Global systolic function and LS are only mildly reduced in pediatric CCSs, and most LS values are within normal range. This makes single LS measurements of limited added value in identifying CCSs at risk for cardiac dysfunction. The utility of strain imaging in the long-term follow-up of CCS remains to be demonstrated. Abstract : Supplemental Digital Content is available in the text.